IMPLEMENTASI AUDIT LINGKUNGAN PADA INDUSTRI PERHOTELAN DI KOTA MALANG - Fenny Handoko (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
This study was conducted to prove the waste treatment by the hospitality industry. Waste processing requires an instrument in supervising waste treatment to conform to standard quality standards. The instrument used is an environmental audit that aims to prove the level of compliance of business and / or activity responsibilities to the legal and policy requirements established by the government. The method used in this research is qualitative descriptive. The sample used in this research is four and five star hotel located in Malang City. The test results indicate that the four-star and five-star hotels have conducted liquid waste treatment done to prevent environmental pollution. Wastewater treatment is monitored and supervised by the government agency, Dinas Lingkungan Hidup. Waste treatment conducted by four-star hotels and waste does not all have waste treatment reports and reports are not all the results in accordance with the standard quality standards. Monitoring and supervision made by the Environment Department of Malang City has not been thorough to the four-star and five-star hotels. The conclusion that can be drawn from this research is the level of compliance about waste treatment at four star and five star hotel is still low.